2017
DOI: 10.1002/bbb.1760
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of sugarcane straw: implications for biomass and bioenergy production

Abstract: Sugarcane straw, consisting of green tops and dry leaves, can be maintained on fields to improve soil quality, or harvested for bioenergy production. The optimum option between these two uses is still uncertain and requires further study. This study, conducted across three crop cycles, provides an assessment of the moisture, nutrients, ash, extractives, cellulose, hemicelluloses, and lignin contents of four sugarcane varieties across seven regions of south‐central Brazil. Suitability of the straw fractions for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(100 citation statements)
references
References 56 publications
(75 reference statements)
1
86
0
13
Order By: Relevance
“…However, other crops are also prominent, such as wheat, cassava, rice, banana, and oil palm. Processing these crops generates large amounts of solid residues, including in‐field or agricultural residues (straw, leaves, and foliage) and agro‐industrial processing residues (bagasse, bunches, and shells) with diverse composition and volume (Table ) …”
Section: The Agro‐industrial Residues In South Americamentioning
confidence: 99%
“…However, other crops are also prominent, such as wheat, cassava, rice, banana, and oil palm. Processing these crops generates large amounts of solid residues, including in‐field or agricultural residues (straw, leaves, and foliage) and agro‐industrial processing residues (bagasse, bunches, and shells) with diverse composition and volume (Table ) …”
Section: The Agro‐industrial Residues In South Americamentioning
confidence: 99%
“…Thus, it is recommended that plant materials have N, Cl, and S in amounts <0, 2, and 3 g kg −1 , respectively, during the combustion process (Surendra et al, 2018). It is important to highlight that energy cane harvesting removes total aboveground biomass (stalks, tops, and dry leaves) and that the tops contain high nutrient concentrations (Menandro et al, 2017). Therefore, knowledge and understanding of nutrients required for energy cane crops is crucial for the development of a sustainable and renewable feedstock for bioenergy production.…”
Section: Biomass Production and Nutrient Removal Of Energy Cane Genotmentioning
confidence: 99%
“…Nutrient concentration in energy cane tops (Table 5) and dry leaves (Table 6) was higher than in stalks and tops, and dry leaf removal from the field may not only diminish the quality of the combustion process (Shahandeh et al, 2011;Tröger et al, 2013;Surendra et al, 2018) but also augment removal of nutrients from the production system (Carvalho et al, 2017b;Bordonal et al, 2018). For sugarcane, recent studies have indicated that part of the sugarcane straw (mainly tops) should be maintained on the field to protect the soil, improve nutrient recycling, and increase biomass yield (Menandro et al, 2017;Bordonal et al, 2018). For sugarcane, recent studies have indicated that part of the sugarcane straw (mainly tops) should be maintained on the field to protect the soil, improve nutrient recycling, and increase biomass yield (Menandro et al, 2017;Bordonal et al, 2018).…”
Section: Nutrient Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…An expressive trend of expansion in this field is expected in the next few years. This is because: (i) Brazil still falls short of fully exploring its energy potential in sugarcane biomass [1,4,5]; (ii) the installed capacity for cogeneration from biomass is 143 GW, representing 9.3% of the domestic energy supply in 2014, and the national commitment is to increase this contribution to 23% by 2030 [6]; (iii) the country has signed international agreements aimed at sustainable development and positive aspects of cogeneration through biomass, but their surveys are narrowed to the use of bagasse as the only energy source.…”
Section: Introductionmentioning
confidence: 99%